Analisis Strategi BPRS Di Sumatera Utara Dalam Menghadapi Kompetisi Di Era Fintech - Tri Auri Yanti; Saparuddin Siregar; Sugianto Sugianto (Proceeding International Seminar of Islamic Studies, 2019)
BPRS as a community trust institution whose existence is able to provide banking services quickly, easily and simply to the community, especially medium, small and micro entrepreneurs in both rural and urban areas. But now the development of BPRS in North Sumatra is starting to lag behind compared to BPRS in other Provinces. This study aims to analyze the BPRS strategy in North Sumatra in the face of competition in the Fintech era. The results showed that the problems that emerged in the era of fintech SRB in North Sumatra consisted of 5 important aspects: Capital, HR, technical, legal / structural aspects, and market / communal effects. Explaining all aspects of the problem results in a priority order: 1) Most SRBs have relatively limited paid up capital; 2) The quality and quantity of human resources must still be improved; 3) Increasingly dynamic regulations; 4) Trust public interest in BPRS tend to be low and 5) Not able to get reliable IT. Whereas the priority of policy strategies that are considered capable of competing in the fintech era consist of: 1) strengthening capital and business scale and increasing the level of efficiency; 2) increase the quantity and quality of BPRS human resources; 3) increase access to banking services by creating digital-based innovations; 4) Increase competitiveness by strengthening competitive and comparative advantages; 5) Strategic Partnership, namely the active role of regulators in connecting the BPRS Industry with third parties.